Electrodeposition of Cadmium from its Different Solution Complexes - Kenawy, I.M.M.; Hafez, M.A.H.; Ghazy, S.E. (Asian Journal of Chemistry, 2010)
New electrolytes for the electrodeposition of highly pure cadmium on platinum and graphite electrodes have been investigated. The deposition was carried out from the metal salt solution in presence of a complexing agent at current density ranges from 0.02 to 1.0 A dm–2 and controlled pH (1–11). Polarographic and X-ray diffraction analyses revealed the purity of cadmium to be 99.9%. The effect of different parameters on electrodeposition was studied. The quantity and quality of the deposit metal was found to depend on the type of the complexing agent used. The baths arrange themselves according to the quality of deposit metal in the following order: tartarate > dithizone > pyrogallol > ammonium chloride ═ ammonium hydroxide > citrate > cyanide ═ dimethylformamide > pyridine ═ o-phenathroline > hydrazine sulphate > methyl violet > diemethylsulfoxide > iodide > 8-hydroxyquinoline > acetylacetone > thiocyanate > dipyridyl > chloride > thiosulphate > bromide > EDTA > oxalate. A mechanism for the cadmium deposition has been proposed and discussed.